2012
DOI: 10.1007/s10464-012-9550-6
|View full text |Cite
|
Sign up to set email alerts
|

How Big is My Neighborhood? Individual and Contextual Effects on Perceptions of Neighborhood Scale

Abstract: Neighborhood is a social and geographic concept that plays an increasingly important role in research and practice that address disparities in health and well-being of populations. However, most studies of neighborhoods, as well as community initiatives geared toward neighborhood improvement, make simplifying assumptions about boundaries, often relying on census geography to operationalize the neighborhood units. This study used geographic information system (GIS) tools to gather and analyze neighborhood maps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
167
2
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(206 citation statements)
references
References 27 publications
14
167
2
9
Order By: Relevance
“…Therefore, different people might form different mental maps of the same built environment and consequently behave differently (Ewing and Handy 2009). Studies have found that there are significant discrepancies between researcher-and resident-defined neighborhood boundaries (Coulton et al 2013;Coulton et al 2001). Further, individuals who live in close proximity can differ markedly from one another in how they define the spatial dimension of their neighborhoods (Coulton et al 2001).…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…Therefore, different people might form different mental maps of the same built environment and consequently behave differently (Ewing and Handy 2009). Studies have found that there are significant discrepancies between researcher-and resident-defined neighborhood boundaries (Coulton et al 2013;Coulton et al 2001). Further, individuals who live in close proximity can differ markedly from one another in how they define the spatial dimension of their neighborhoods (Coulton et al 2001).…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…The survey questions asked respondents general demographic information, how long they had lived in the neighborhood, their sense of belonging to the neighborhood and larger community, neighborhood boundaries and name, any neighborhood issues, their civic participation, what might inhibit their involvement in a neighborhood association, and how they would prefer to communicate (or not) with a neighborhood association and with their neighbors. The survey used and modified questions from previous studies on neighborhood organizations and sense of community (Chavis & Wandersman, 1990;Coulton et al, 2012;Glynn, 1981;Hampton et al, 2011;Martinez et al, 2002;Perkins & Long, 2002;Saguaro Seminar, 2000;Sigmon, Whitcomb, & Snyder, 2002). Surveys were anonymous unless the person indicated that we could contact him or her for a future interview.…”
Section: Methodsmentioning
confidence: 99%
“…These boundaries can change over time and residents can define their neighborhood differently (Taylor, 2012). It is notable that those who take a larger view when defining their neighborhood tend to be people who are more engaged with the neighborhood (Coulton et al, 2012). Having a name and boundaries are helpful when moving from informal relationships to more formal ones and engaging with local government (Taylor, Gottfredson, & Brower, 1984).…”
Section: Sense Of Community and Neighborhood Organizingmentioning
confidence: 99%
“…Cognitive mapping exercises like the one employed here have been used extensively to explore residents' perceptions of the built environment [39][40][41][42], how perceptions vary among individuals and groups [43][44][45][46][47], and how perceptions may change over time [48][49][50]. Tuan [51] saw cognitive maps as a way to translate residents' "imagined world" of space and place into physical form.…”
Section: Resident Perceptionsmentioning
confidence: 99%